VUMA: A Visual User Modeling Approach for the Personalization of Adaptive Systems - CONLAN, OWEN (Springer, 2008)
Current approaches to explicit user modelling are generally time consuming and tedious for the user. Oftentimes poor usability and overly long questionnaires deter the end user from reusing such modelling tools, thus only facilitating explicit personalisation once as they enter the system. This paper proposes a visual approach to user modelling resulting in the VUMA (Visual User Modelling Approach) tool that can be used in a playful and dynamic manner repeatedly during a user?s engagement with a personalisation system. This work proposes and evaluates a visually empowering, usable, highly configurable and playful user modelling interface that is utilised to elicit user interests and preferences in a chosen knowledge domain.
PUBLISHED
Keywords: visual user modelling; user profiling; user interface; personalisation